Fellow of the European board of ophthalmology glaucoma examination and diploma (FEBOS-Gl): update on 8 years of experience and future perspectives - Sunaric Mégevand, Gordana; Bron, Alain M.; Topouzis, Fotis (Frontiers in Medicine, 2023)
Glaucoma is the leading cause of irreversible blindness worldwide. Early diagnosis and appropriate management of the disease are essential to avoid a significant impact on the quality of life of millions of patients and the socioeconomic impact on societies. Education is the hallmark of good medical care. The European Glaucoma Society (EGS) has dedicated significant efforts to provide means of improving education, training, and testing knowledge in the field of glaucoma. The Fellow of the European Board of Ophthalmology Subspecialty (FEBOS)-Glaucoma examination, introduced and organized yearly by the EGS since 2015 in collaboration with the European Board of Ophthalmology (EBO), has become a valuable tool for increasing overall knowledge in the field. Over the 8 years of experience, several updates and new projects have emerged around the examination to further increase the overall quality of education, training, and knowledge in the field of glaucoma in Europe, particularly in UEMS and associated countries. This article discusses in detail the various projects and measures introduced by the EGS.